Frequency and nature of potentially harmful preventable problems in primary care from the patient's perspective with clinician review: a population-level survey in Great Britain. Issue 6 (13th June 2018) - Stocks, Susan Jill; Donnelly, Ailsa; Esmail, Aneez; Beresford, Joanne; Luty, Sarah; Deacon, Richard; Danczak, Avril; Mann, Nicola; Townsend, David; Ashley, James; Gamble, Carolyn; Bowie, Paul; et al.
Abstract : Objectives: To estimate the frequency of patient-perceived potentially harmful problems occurring in primary care. To describe the type of problem, patient predictors of perceiving a problem, the primary care service involved, how the problem was discussed and patient suggestions as to how the problem might have been prevented. To describe clinician/public opinions regarding the likelihood that the patient-described scenario is potentially harmful. Design: Population-level survey. Setting: Great Britain. Participants: A nationally representative sample of 3975 members of the public aged ≥15 years interviewed during April 2016. Main outcome measures: Counts of patient-perceived potentially harmful problems in the last 12 months, descriptions of patient-described scenarios and review by clinicians/members of the public. Results: 3975 of 3996 participants in a nationally representative survey completed the relevant questions (99.5%). 300 (7.6%; 95% CI 6.7% to 8.4%) of respondents reported experiencing a potentially harmful preventable problem in primary care during the past 12 months and 145 (48%) discussed their concerns within primary care. This did not vary with age, gender or type of service used. A substantial minority (30%) of the patient-perceived problems occurred outside general practice, particularly the dental surgery, walk in clinic, out of hours care and pharmacy. Patients perceiving a potentially harmful preventable problem were eight times more likely to have 'no confidence and trust in primary care' compared with 'yes, definitely' (OR 7.9; 95% CI 5.9 to 10.7) but those who discussed their perceived-problem appeared to maintain higher trust and confidence. Generally, clinicians ranked the patient-described scenarios as unlikely to be potentially harmful. Conclusions: This study highlights the importance of actively soliciting patient's views about preventable harm in primary care as patients frequently perceive potentially harmful preventable problems and make useful suggestions for their prevention. Such engagement may also help to improve confidence and trust in primary care.